2007
DOI: 10.5194/nhess-7-405-2007
|View full text |Cite
|
Sign up to set email alerts
|

An automatic monitoring network installed in Tuscany (Italy) for studying possible geochemical precursory phenomena

Abstract: Abstract. Since late 2002, a continuous automatic monitoring network (CAMN) was designed, built and installed in Tuscany (Italy), in order to investigate and define the geochemical response of the aquifers to the local seismic activity. The purpose of the investigation was to identify eventual earthquake precursors. The CAMN is constituted by two groups of five measurement stations each. A first group has been installed in the Serchio and Magra graben (Garfagnana and Lunigiana Valleys, Northern Tuscany), while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Using InSAR and SAR data, co-seismic rupture and surface deformations were mapped in the epicentral and surrounding regions of the Wenchuan Earthquake (Huang 2008, Hao et al 2009, Kobayashi et al 2009, Li 2009, Ren et al 2009, Wu et al 2010. Anomalous changes on the ground, in the atmosphere and in the ionosphere have been observed associated with several earthquakes that occurred in China, Russia, Japan, Taiwan and Europe (Varotsos and Alexopoulos 1984a, 1984b, Liu et al 2000, Matsuda and Ikeya 2001, Singh et al 2006, 2007a, 2007b, Walia et al 2006, Yasuka et al 2006, Cioni et al 2007, Dutta et al 2007, Ghosh et al 2007, Omori et al 2007, Inan et al 2008, Tronin 2010). …”
mentioning
confidence: 99%
“…Using InSAR and SAR data, co-seismic rupture and surface deformations were mapped in the epicentral and surrounding regions of the Wenchuan Earthquake (Huang 2008, Hao et al 2009, Kobayashi et al 2009, Li 2009, Ren et al 2009, Wu et al 2010. Anomalous changes on the ground, in the atmosphere and in the ionosphere have been observed associated with several earthquakes that occurred in China, Russia, Japan, Taiwan and Europe (Varotsos and Alexopoulos 1984a, 1984b, Liu et al 2000, Matsuda and Ikeya 2001, Singh et al 2006, 2007a, 2007b, Walia et al 2006, Yasuka et al 2006, Cioni et al 2007, Dutta et al 2007, Ghosh et al 2007, Omori et al 2007, Inan et al 2008, Tronin 2010). …”
mentioning
confidence: 99%
“…5). That latter procedure -somehow analogous to one previously used by Cioni et al (2007) for identifying earthquake-related signals in time-series of temperature, electrical conductivity and CO 2 concentration of a specific outlet -made readily apparent certain distinct correlation-regimes, which shall be given detailed discussion in the next section.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…This rather simple technique has been previously used by Cioni et al (2007), for identifying earthquake-related signals within time records of certain physical and chemical parameters (temperature, water electrical conductivity, CO 2 concentration) of a specific groundwater outlet.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, anomalous changes to the ground, atmosphere and ionosphere, observed by both Earth-and space-based instrumentation, were found to be associated with several earthquakes that occurred in China, Taiwan, Europe and Japan (Walia et al 2006, Yasuoka et al 2006, Cioni et al 2007, Omori et al 2007, Sharma et al 2008, Anagnostopoulos et al 2010b, Hayakawa and Hobara 2010, Singh et al 2010a. These recent reported pronounced changes in the various surface and atmospheric parameters a few days prior to various earthquakes provide a strong evidence of lithosphere-atmosphere-ionosphere coupling.…”
mentioning
confidence: 95%
“…During the last 100 years there has been an average of about 18 large earthquakes (magnitude 7.0-7.9) in each year (http://earthquake.usgs.gov). Recent studies using multisensor data have shown that pronounced changes occur on the Earth's surface, meteorological and atmospheric, and ionospheric parameters associated with earthquakes which occurred in China, Russia, Japan, Taiwan and Europe (Liu et al 2000, Matsuda and Ikeya 2001, Cervone et al 2004, Singh et al 2006a,b,c, Walia et al 2006, Yasouka et al 2006, Cioni et al 2007, Dutta et al 2007, Ghosh et al 2007, Omori et al 2007, Inan et al 2008. These changes can be utilized to obtain early information about an impending earthquake.…”
Section: Introductionmentioning
confidence: 99%